Knowledge, attitude, and practice regarding rabies among animal bite patients attending a tertiary care hospital in central India: a cross-sectional study - Jain, Mudita; Jangale, Gopal; Gawande, Avinash; Narlawar, Uday (International Journal Of Community Medicine And Public Health, 2025)
Background: Rabies is a 100% fatal but preventable viral zoonotic disease, primarily transmitted through the bite of infected dogs. India accounts for a large share of global rabies deaths, attributed to low awareness, poor healthcare-seeking behavior, and reliance on traditional remedies. Understanding the knowledge, attitude, and practices (KAP) of individuals exposed to animal bites is crucial for rabies control. Objective was to assess the KAP regarding rabies among animal bite patients attending the anti-rabies clinic of a tertiary care hospital in central India. Methods: A cross-sectional study was conducted among 210 animal bite patients using a pre-tested semi-structured questionnaire during December 2024. Universal sampling was applied. Data on socio-demographic characteristics and KAP were collected through face-to-face interviews and analyzed using descriptive statistics. Results: Among participants, 64.8% were male and 62.9% resided in rural areas. While 78.6% had heard of rabies and 71.9% knew about transmission via dog bites, only 48.1% were aware of wound washing. Though 68.1% initiated the anti-rabies vaccine (ARV), only 52.4% completed it. Just 30.3% of pet owners had vaccinated their pets. Conclusions: Despite moderate awareness, significant gaps in rabies-related practices exist. Community-level health education and improved vaccine compliance are vital for rabies elimination.